Dyeing (Rini) activity as intangible cultural heritage identity and sustainability patterns among dyers community in Kofar Mata Kano, Nigeria - Young, Abubakar Sadiq (2021)
For centuries, Kofar Mata intangible cultural heritage (ICH)-dyeing has been Hausaland famous skill activity in textile making and trading. This has not only attracted people from Africa and other parts of the world to Kano but it has made the town strategic in commercial activities. Although, this one-time booming industry is on the verge of extinction due to new technology and cheap importation of textiles material, dyers struggle with challenges to keep up the ancient practice. This study explored dyeing (rini) activity as intangible cultural heritage identity and sustainability patterns among dyers community in their continuous engagement in Kofar Mata, Kano, Nigeria. Specifically, the study explores to understand the reasons for the continuous engagement in dyeing pits from dyers community perspective, to understand the sustainable benefits to dyers and its community, to also identify the challenges hindering dyers engagement in the Kofar Mata dyeing, and strategies or measure to be taken to safeguard the traditional ICH dye practices. The research used the qualitative case study approach and data were collected through in-depthinterviews with six (6) key informants, and six (6) other informants for Focus Group Discussion and observation. Findings revealed that dyers factors influencing the continuous engagement in the Kofar Mata dyeing is a clear manifestation of cultural pride such as ancestral knowledge and family legacy, and cultural identity. Challenges hindering the dyers engagement in the dyeing activities are critical political and oppressive imbalance from the political class, lack of proper awareness among the dyers and environmental factors such as territorial encroachment of the dye pits landscape. The finding of the study also revealed sustainable benefits of dyers at Kofar Mata brings about social cohesion among all stakeholders; the dye pits residual is use as medicinal value to the community; and also serves as tourism potentials; is an attire that portrait the social class dimension of fashion with identity in the society. Strategies or measure to safeguard dyers of the dyeing industry are that proper recognition of dyers by government policy in terms of logistic supports, motivation, restructuring or introduction of modern technology into the ICH dyeing industry; securing the dye pits territorial dimensions; and opening a window of opportunities in marketability of the ICH products. Though dyers continuous engagement in Kofar Mata were characterized by critical political manipulation and oppression of policy makers in authority, however, addressing these issues will improve interaction among dyers and authorities. Stipends to these dyers as the Living Human Treasure (LHT) will enhance and improve their general wellbeing. The study concluded that the LHT in Kofar Mata ICH are able to exhibit their practical expertise in dyeing skill, improved designing and marketability in their profession to enhance their socio- economic wellbeing, and at the same time influence and draw the authority’s recognition to consider heritage practice to understand the sustainable benefits to dyers and its community as community development in the aspect of ICH Kofar Mata dyeing pits. The findings offered theoretical and policy implication that is core in understanding the dyers participation in safeguarding ICH in Kano, as their cultural life and identity. The findings offered theoretical and policy implication that is core in understanding the dyers participation in safeguarding ICH in Kano, as their cultural life and identity. Finally, the outcome of this study provides new knowledge on intangible cultural heritage and an important insight for relevant government cultural resource centers such as Kofar Mata dyeing industry. This also relate to the institutionalizing the UNESCO/ICH Convention 2003 for the Safeguarding of Intangible Cultural Heritage (CSICH) for sustainable community development, based on the community-based cultural heritage and enforce new policies towards achieving sustainability for this industry in Kano, Nigeria.